2011
DOI: 10.1364/ao.50.006452
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-wave terahertz phase imaging using a far-infrared laser interferometer

Abstract: Terahertz phase imaging can reveal the depth information of an optically opaque object and provide much better contrast for weak-absorption materials. We demonstrate a continuous-wave terahertz interferometric imaging method in which a far-infrared laser interferometer is used to measure the phase distribution with diffraction-limited lateral resolution and subwavelength axial resolution. An improved four-step phase-shifting algorithm is introduced to retrieve the phase map with very high accuracy and low dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…where f is the carrier frequency, which could give the additional information to an ordinary THz amplitude image. 10 In this letter, we report an observation of geometrically induced phase shift of THz waves and its application to THz imaging of sub-wavelength-scale objects. In an experiment of THz wave generation from semiconducting InAs structure, we found that the pulses radiated from emitters of subwavelength scale are temporally shifted compared to the ones from large emitters.…”
mentioning
confidence: 97%
“…where f is the carrier frequency, which could give the additional information to an ordinary THz amplitude image. 10 In this letter, we report an observation of geometrically induced phase shift of THz waves and its application to THz imaging of sub-wavelength-scale objects. In an experiment of THz wave generation from semiconducting InAs structure, we found that the pulses radiated from emitters of subwavelength scale are temporally shifted compared to the ones from large emitters.…”
mentioning
confidence: 97%
“…It is reported that phase imaging is more sensitive to the component pattern of a specimen than amplitude and timeof-flight imaging [24]. In [25], phase imaging is used to reveal the depth information of an optically opaque object and provides much better contrast for weak-absorption materials. The spectral phase, derived from a typical time-domain terahertz waveform by Fourier transform, is essentially linear [26].…”
Section: Introductionmentioning
confidence: 99%
“…Phase distribution allows the reconstruction of the Teflon object thickness pattern in low SNR registration conditions [27]. In summary, amplitude spectra are suitable for characterization of strong absorption materials [23], whereas phase spectra contain more significant information and exhibit linear behavior, thus outperforming amplitude spectra for weak-absorption and transparent materials, low SNR, and thin-film cases [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Combining this interferometer with our imaging systems, a continuous-wave THz phase imaging system53 is now under construction.…”
Section: Resultsmentioning
confidence: 99%